Alteration of Phenolic and Volatile Compounds of Tea Leaf Extract by Tyrosinase and β-Glucosidase during Preparation of Ready-to-Drink Tea on Farm - Dea Risfika Faustina; Rachmad Gunadi; Aprilia Fitriani; Supriyadi Supriyadi (International Journal of Food Science)
The manufacturing of ready-to-drink black tea was through a long process, up to 14-18 hours. There was an alternative way to produce RTD black tea directly on the farm to reduce time production and improve the quality of black tea using exogenous enzymes, i.e., tyrosinase and β-glucosidase. Tyrosinase was investigated for the ability to improve the color of tea extract by oxidize the phenolic content of green tea leaves to theaflavin and thearubigin, and β-glucosidase can enhance the volatile compounds by hydrolyze glycosidic bonds in tea leaves. Incubation of tea leaf extract with tyrosinase produces a high content of theaflavin and good color of tea extract but lowered the antioxidant activity. According to the TF/TR ratio values, tyrosinase treated tea leaf extract was in the best quality tea range. The use of β-glucosidase showed an increase in the proportion of good volatile compounds of linalool, linalool oxide, methyl salicylate, and β-damascenone.